Kritik Sosial dalam Musik (Analisis Semiotika Makna Lirik Lagu “Seperti Rahim Ibu” Karya Band Efek Rumah Kaca) - Ningsih, Setia; Setyawan, Agus; Ansori, Teguh (Journal of Communication Studies, 2024)
One of the functions of music is as a mass communication medium. Music can record reality and launch social criticism. This research is entitled "Social Criticism in Music (Semiotic Analysis in the Lyrics of the Song "Like Rahim Ibu" by the band Efek Rumah Kaca). This research aims to understand the meaning and explore social criticism in the lyrics of the song Like Rahim Ibu by Efek Rumah Kaca and Najwa Shihab through study of semiotic analysis theory. The theoretical basis used in this research is Roland Barthes' semiotic analysis theory. The method used is a descriptive qualitative method using a social approach. The data collection technique in this research uses the documentation method , autobiographies, memoirs, diaries, articles, magazines, and other data that supports this research. This research uses Roland Barthes' semiotic analysis. The results of this researcher conclude that the lyrics of the song "Like a Mother's Womb" are a form of implicit social criticism the songwriter wanted to convey to listeners and music lovers